PENGEMBANGAN MEDIA PEMBELAJARAN LAPISAN BUMI BERBASIS AUGMENTED REALITY - Deni Andreyan Feneza; Tri Widodo (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
Learning about the layers of the earth at junior high school (SMP) level often experiences problems. Limited teaching aids and visual media make learning less supportive. The current learning process must go hand in hand with technological developments. Research in developing Augmented Reality-based learning media for earth layers aims to introduce various types of earth layers and their characteristics. The development of this learning media uses the Research and Development (R&D) method with the ADDIE development model. This learning media has gone through a media expert validation test process by obtaining a score of 79% in the media category "suitable" for use. The material expert validation test with a score of 85% was included in the material category "very suitable" for use. Furthermore, the results of the user test totaling 10 people obtained a score of 81% in the category "very suitable" for use.